PERBEDAAN PERSENTASE PEMBERIAN RANSUM ANTARA SIANG DAN MALAM TERHADAP PERFORMA AYAM JANTAN TIPE MEDIUM DI KANDANG POSTAL - Khaira Nova; Riyanti Riyanti; Dian Septinova; Purnama Edy Santosa (JURNAL ILMIAH PETERNAKAN TERPADU, 2019)
The objective of this experiment  was to determine the effects of different percentage of ration between day and night to male chicken medium type performance;  the best level of percentage of ration that given between the day and night in chicken coop. A total of one hundred and forty four day-old male chicks medium type were divided into 3 treatments and 6 replications, each treatment consist of 8 male chickens. The treatments were ration that given 30% during the day and 70% the night; ration that given 50% during the day and 50% the night; ration that given 70% during the day and 30% the night. This research was conducted from August through October 2018 in Integrated Laboratory Department of Animal Husbandry, Faculty of Agriculture, University of Lampung.  Data were subjected to analysis variance. Significant was considered at 5% level of probability. The results showed, percentage ration between day and night signicant influence feed consumption (P <0.05), but not significant effect to body weight and feed conversion ratio. The percentage of ration given 30% during  day and 70%  night is the best treatment influence feed conversion ratio (2,41) with feed consumption 1.738.03 g/bird  and body weight 718,58 g/bird. Keywords : Male chickens, Ration percentage, Chicken coop